Projectile dynamics in sport - White, C. (Routledge studies in sports performance analysis, 2011)
How can we predict the trajectory of a baseball from bat to outfield? How do the dimples in a golf ball influence its flight from lee to pin? What forces determine the path of a soccer ball steered over a defensive wall by an elite player? An understanding of the physical processes involved in throwing, hitting, firing and releasing sporting projectiles is essential for a full understanding of the science that underpins sport. This is the first book (o comprehensively examine those processes and to explain the factors governing the trajectories of sporting projectiles once they arc set in motion. From a serve in tennis to the flight of a 'human projectile' over a high jump bar. this book explains the universal physical and mathematical principles governing movement in sport, and then shows how those principles arc applied in specific sporting contexts. Divided into two main sections, addressing theory and application respectively, the book explores key concepts such as: • friction, spin, drag, impact and bounce; • computer and mathematical modelling; • variable sensitivity; • the design of sports equipment; • materials science. Richly illustrated throughout, and containing a wealth of research data as well as worked equations and examples, this book is essential reading for all serious students of sports biomechanics, sports engineering, sports technology, sports equipment design and sports performancc analysis.